2012
DOI: 10.1093/ntr/nts080
|View full text |Cite
|
Sign up to set email alerts
|

Dependence and Withdrawal-Induced Craving Predict Abstinence in an Incentive-Based Model of Smoking Relapse

Abstract: Introduction: Understanding factors that render some individuals more vulnerable to smoking relapse during the early stages of a quit attempt is critical to tailoring treatment efforts. Development of laboratory models of relapse can provide a framework for identifying underlying mechanisms that may contribute to vulnerability. Here, we explored predictors of abstinence in a novel incentive-based model of relapse.Methods: Fifty-six nontreatment seeking daily smokers completed several nicotine dependence measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 39 publications
5
39
2
1
Order By: Relevance
“…Interestingly, higher craving during the abstinence session was actually associated with lower likelihood of lapse during CM. This is in contrast with several studies that have demonstrated associations between increased craving and poorer abstinence outcomes in laboratory-based studies and smoking cessation trials (Bold et al 2013; Sweitzer et al 2013a; Van Zundert et al 2012) but see also (Wray et al 2013). Thus, it is possible that the availability of monetary incentives for abstinence may have enhanced extrinsic motivation to quit and thereby disrupted the association between subjective craving for cigarettes (and potentially increased striatal anticipation for smoking reward) and actual smoking behavior.…”
Section: Discussioncontrasting
confidence: 85%
“…Interestingly, higher craving during the abstinence session was actually associated with lower likelihood of lapse during CM. This is in contrast with several studies that have demonstrated associations between increased craving and poorer abstinence outcomes in laboratory-based studies and smoking cessation trials (Bold et al 2013; Sweitzer et al 2013a; Van Zundert et al 2012) but see also (Wray et al 2013). Thus, it is possible that the availability of monetary incentives for abstinence may have enhanced extrinsic motivation to quit and thereby disrupted the association between subjective craving for cigarettes (and potentially increased striatal anticipation for smoking reward) and actual smoking behavior.…”
Section: Discussioncontrasting
confidence: 85%
“…Forward stepwise regression with a probability of 0.2 for removal and 0.1 for entry was used to select predictors for a logistic regression model (STATA logistic) of dichotomized 7-day relapse. Sex, age, and nicotine dependence level (Heatherton et al, 1991) were entered as baseline candidate predictors of relapse (Gourlay et al, 1994;Hymowitz et al, 1997;Japuntich et al, 2011;Sweitzer et al, 2013). Change scores (abstinence challenge minus smoking satiety) for paired data collected during abstinence challenge (MNWS, QSU-Brief, PANAS Positive, PANAS Negative, task performance (accuracy and response time), right DLPFC, left DLPFC, MF/CG, vmPFC, and PCC) were also included in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we examined task performance and BOLD signal acquired during performance of 3-back trials (minus BOLD signal acquired during performance of 0-back trials to account for task-related cognitive processes other than working memory). We required age and nicotine dependence to be entered based on clinical relevance (Hymowitz et al, 1997;Sweitzer et al, 2013); sex was nonsignificant, and allowed to dropout. Following logistic regression, receiver operating characteristic (ROC) analysis was used to assess the predictive potential of the models (Steyerberg, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Scores range from 0–10 with higher scores indicating higher levels of dependence. Past work illustrates that FTND demonstrates good reliability and predictive and convergent validity to other measures of nicotine dependence [33] and dependence-relevant processes, including nicotine withdrawal [34], craving [35], biomarkers indicative of tobacco exposure [36], and abstinence following cessation [33, 37, 38]. …”
Section: Methodsmentioning
confidence: 99%